Engineering pressure retarded osmosis membrane bioreactor (PRO-MBR) for simultaneous water and energy recovery from municipal wastewater - Liu, Shuyue (2023)
Osmotic membrane bioreactors (OMBR) have gained increasing interest in wastewater treatment and reclamation due to their high product water quality and fouling resistance. However, high energy consumption (mostly by draw solution recovery) restricted the wider application of OMBR. Herein, we propose a novel pressure retarded osmosis membrane bioreactor (PRO-MBR) for improving the economic feasibility. In comparison with conventional FO-MBR, PRO-MBR exhibited similar excellent contaminants removal performance and comparable water flux. More importantly, a considerable amount of energy can be recovered by PRO-MBR (4.1 kWh/100 m2·d), as a result of which, 10.02% of the specific energy consumption (SEC) for water recovery was reduced as compared with FO-MBR (from 1.42 kWh/m3 to 1.28 kWh/m3). Membrane orientation largely determined the performance of PRO-MBR, higher power density was achieved in AL-DS orientation (peak value of 3.4 W/m2) than that in AL-FS orientation (peak value of 1.4 W/m2). However, PRO-MBR suffered more severe and complex membrane fouling when operated in AL-DS orientation, because the porous support layer was facing sludge mixed liquor. Further investigation revealed fouling was mostly reversible for PRO-MBR, it exhibited similar flux recoverability (92.4%) to that in FO-MBR (95.1%) after osmotic backwash. Nevertheless, flux decline due to membrane fouling is still a restricting factor to power generation of PRO-MBR, its power density was decreased by 38.2% in the first 60 min due to the formation of fouling. Overall, in perspective of technoeconomic feasibility, the PRO-MBR demonstrates better potential than FO-MBR in wastewater treatment and reclamation and deserves more research attention in the future.